Spectral properties of non-homogeneous Timoshenko beam and its controllability - Sklyar, G.M.; Szkibiel, G. (Механика твердого тела, 2007)
Controllability of slowly rotating non-homogeneous beam clamped to a disc is considered. It is assumed that at the beginning the beam remains at the position of rest and it is supposed to rotate by the given angle and achieve desired position. The rotor of propelling engine is in the middle of the disk. The movement is governed by the system of two di erential equations with non-constant coe cients: linear mass density, exural rigidity, rotational inertia and shear sti ness. To solve the problem of controllability, the spectrum of the operator generating the dynamics of the model is studied. Then the problem of controllability is reduced to the moment problem that is, in turn, solved with the use of the asymptotics of the spectrum and Ullrich Theorem.